A self-supported electrochemical sensor for simultaneous sensitive detection of trace heavy metal ions based on PtAu alloy/carbon nanofibers. Issue 48 (29th November 2017) - Zhang, SongGe; Zhu, Han; Ma, PiMing; Duan, Fang; Dong, WeiFu; Du, MingLiang
Abstract : The key issue in efficient electrochemical detection of trace heavy metal ions (HMIs) is to design hierarchical nanostructure electrodes with high sensitivity and low detection limit. Abstract : The key issue in efficient electrochemical detection of trace heavy metal ions (HMIs) is to design hierarchical nanostructure electrodes with high sensitivity and low detection limit. In this study, bimetallic PtAu alloy nanoparticles (PtAuNPs) with uniform size and distribution were constructed in electrospun carbon nanofibers (CNFs) by combining an electrospinning procedure and an in situ thermal reduction process. The PtAu/CNF membrane can be directly used as a sensor electrode for simultaneous detection of trace Cd 2+, Pb 2+, and Cu 2+ by square wave anodic stripping voltammetry (SWASV). The prepared PtAu/CNF membrane is capable of simultaneously detecting Cd 2+, Pb 2+, and Cu 2+ with a sensitivity of 0.10 μM and correlation coefficients of 0.976, 0.993, and 0.976, respectively, indicating high sensitivity and good linear relation. The excellent sensitivity and low detection limit for HMI detection were ascribed to the high conductivity of CNFs, fast response of PtAu alloy NPs, and high specific surface area of the hybrid structure. The present research provides a convenient and efficient way to construct new sensors for simultaneous trace detection of HMIs.